To solve the expression
\[ \frac{(3.6 \times 10^5) \times (1.5 \times 10^{-8})}{(2.5 \times 10^{-4})} \]
we can follow these steps:
-
Multiply the numerators: \[ 3.6 \times 1.5 = 5.4 \] For the powers of ten: \[ 10^5 \times 10^{-8} = 10^{5 + (-8)} = 10^{-3} \] So the product in the numerator is: \[ 5.4 \times 10^{-3} \]
-
Now we divide by the denominator: \[ \frac{5.4 \times 10^{-3}}{2.5 \times 10^{-4}} \] First, perform the division on the numbers: \[ \frac{5.4}{2.5} = 2.16 \] For the powers of ten: \[ 10^{-3} \div 10^{-4} = 10^{-3 - (-4)} = 10^{-3 + 4} = 10^1 \]
-
Combine the results: \[ 2.16 \times 10^1 \]
Thus, the final expression in scientific notation is: \[ 2.16 \times 10^1 \]
The correct answer is: b (2.16 × 10^1).